Genetic analysis of the role of the asparaginyl hydroxylase factor inhibiting hypoxia-inducible factor (FIH) in regulating hypoxia-inducible factor (HIF) transcriptional target genes [corrected]. - Stolze, I; Tian, Y; Appelhoff, R; Turley, H; Wykoff, C; Gleadle, J; Ratcliffe, P (2004)
Hypoxia-inducible factor (HIF) is a heterodimeric transcription factor that directs a broad range of cellular responses to hypoxia. Recent studies have defined a set of 2-oxoglutarate and Fe(II)-dependent dioxygenases that modify HIF-alpha subunits by prolyl and asparaginyl hydroxylation. These processes potentially provide a dual system of control, down-regulating both HIF-alpha stability and transcriptional activity. Although genetic analyses in both primitive organisms and mammalian cells have demonstrated a critical role for the prolyl hydroxylase pathway in the regulation of HIF, analogous studies have not been performed on the HIF asparaginyl hydroxylase pathway, and its role in directing the expression of endogenous HIF transcriptional targets has not yet been clearly defined. Here we demonstrate, using small interfering RNA-mediated FIH suppression and controlled overexpression by a doxycycline-inducible system, that alterations in FIH expression in both directions have reciprocal effects on the expression of a range of HIF target genes. These effects were observed in normoxic and severely hypoxic cells but not anoxic cells. Evidence for FIH activity in severely hypoxic cells contrasted with results for the prolyl hydroxylase PHD2, suggesting that these enzymes display different oxygen dependence in vivo, with PHD2 requiring higher levels of oxygen for biological activity. Our results demonstrate an important physiological role for FIH in regulating HIF-dependent target genes over a wide range of oxygen tensions and indicate that inhibition of FIH has the potential to augment HIF target gene expression even in severe hypoxia.